Performance Quality Management in an Islamic Perspective: Literature Study and Responses of Economists - Aslami, Nuri (International Conference on Sciences Development and Technology, 2022)
One problem that arises in the management of sharia institutions is that the quality management model used is the same as the quality management of conventional institutions in general. Therefore we need innovation in quality management. Implementing Sharia quality management in Islamic institutions is expected to improve the performance and quality of institutions. This study aims to obtain a cycle of implementing a sharia-based performance quality management system, analyze research maps related to performance quality management in an Islamic perspective in Indonesia in a qualitatively descriptive manner in the last two years, and analyze the response of Islamic Economics academics to performance quality management in an Islamic perspective. Using qualitative research with content analysis and focus discussion groups with economists, 16 articles were published in journals from 2021 to 2022. This study found that the PDCA cycle was developed into eight steps for implementing performance quality management in an Islamic perspective with six orientations: worship orientation, internal process orientation, learning orientation, talent orientation, customer orientation, and wealth orientation.